Aficionado's Southwestern Cooking - Johnson, Ronald (Albuquerque, NM Living Batch Press, 1993)
First published in 1968, this classic book foreshadowed the regional haute cuisine that became popular twenty years later.Previously published as Southwestern New and Old.
Reprint ed. of: Southwestern cooking, new and old. Rev. ed. 1985.
Includes index.
75958
Keywords: Cookery, American -- Southwestern style; Cookery, Mexican